Analisis Sentimen Publik Terhadap Penurunan Jumlah Pernikahan di Indonesia menggunakan Algoritma K-Nearest Neighbors (KNN) - Lailany, Afyra Ar’bah; Lestari, Sri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Marriage in Indonesia is an important aspect of its culture and society. However, in recent years, there has been a significant decline in the number of marriages in the country. To understand people's views on this phenomenon, this research aims to conduct a sentiment analysis regarding the decline in the number of marriages in Indonesia. A decrease in the number of marriages can cause various economic problems. There are certain factors that contribute to this change, such as shifts in values or economic factors. Knowing views on this matter is important for formulating appropriate policies and finding effective solutions. The method used in this research is analysis using the K-Nearest Neighbors (KNN) algorithm. Data will be collected through comments on Tiktok social media pages. The opinion data obtained will be processed using the KNN algorithm to classify positive, negative or neutral sentiment regarding the decline in the number of marriages. The data used amounted to 2,000 data, and were processed using the CRISP-DM method.